Individual evaluation of income growth accounting for internal and external reference points. - Bárcena-Martín, Elena María (My University, 2023)
In this paper we address the evaluation of individual income growth in Spain during the period 2009-2020 providing a framework in which progressive growth and re-ranking are identified at the individual level taken into consideration internal and external benchmarks. We have shown that despite the fact that the annual income changes between 2009-2020 in Spain have been always progressive, in times of crisis this progressiveness has not counterbalanced the reranking, thus leading to an increase in overall inequality, and therefore to an increase in the average level to which individuals are left behind. Moreover, we have shown that income change evaluation has not been the same for individuals in different parts of the distribution. Thus, individuals from the lower and lower-middle class have experienced progressive changes in income, derived from increases in their relative income versus losses in the relative income of individuals higher up in the income distribution. However, upper-middle and upper class individuals have experienced lower income losses than their reference group, also resulting in progressive income changes. Additionally, we have revealed that the reduction in the degree to which the individuals of the different classes have been left behind depends on their positional mobility. The moderate mobility of lower-class individuals, together with the high progressivity in their income changes, has allowed them to considerably reduce the distance with respect to the best positioned individuals, that is, they are less behind. However, individuals from the lower-middle class, who experience a lower degree of progressivity and high mobility, widen their gap with respect to the best positioned, falling further behind. Lastly, upper-middle and upper-class individuals also lag further behind, mainly as a consequence of comparatively low progressivity in their income changes, accompanied by high mobility in the case of the upper-middle class.
Keywords: Renta - Aspectos sociales; Poder adquisitivo; Situación socioeconómica; Spain; External and internal benchmark; Relative assessment; Growth